Memory reconsolidation in aversive and appetitive settings - Reichelt, Amy C.; Lee, Jonathan L. (Frontiers in Behavioral Neuroscience, 2013)
Memory reconsolidation has been observed across species and in a number of behavioural paradigms. The majority of memory reconsolidation studies have been carried out in pavlovian fear conditioning and other aversive memory settings, with potential implications for the treatment of post-traumatic stress disorder. However, there is a growing literature on memory reconsolidation in appetitive reward-related memory paradigms, including translational models of drug addiction. While there appears to be substantial similarity in the basic phenomenon and underlying mechanisms of memory reconsolidation across unconditioned stimulus valence, there are also notable discrepancies. These arise both when comparing aversive to appetitive paradigms and also across different paradigms within the same valence of memory. We review the demonstration of memory reconsolidation across different aversive and appetitive memory paradigms, the commonalities and differences in underlying mechanisms and the conditions under which each memory undergoes reconsolidation. We focus particularly on whether principles derived from the aversive literature are applicable to appetitive settings, and also whether the expanding literature in appetitive paradigms is informative for fear memory reconsolidation.